Their Yuletide healing [large type] - Obenhaus, Mindy (Love inspired., 2021)
"Foster mom Rae Girard's determined to make her children's first Christmas with her the best they've ever had- and she's shocked when the town scrooge, attorney Cole Heinsohn, offers to pitch in. Rae's young charges have melted Cole's heart, and he wants them to experience the special day he never had. But when disaster strikes, an imperfect holiday might bring them something better: a family."--Back cover.